Dynamic change handling for inter-organisational workflows in open virtual eMarketplaces. (5th April 2010) - Ahn, Hyung Jun; Lee, Habin; Kim, Hanseup; Park, Sung Joo; , John Shepherdson
Electronic marketplaces (eMarketplaces) help companies react more flexibly to customer demands by automating various types of transactions online. However, despite this advantage, eMarketplaces pose significant challenges in respect of change management for the participating companies, due to lack of central control, information opacity and heterogeneity of information systems. In order to address these problems, this paper presents an agent-based framework for handling change in dynamic inter-organisational workflows (ADIOF) in virtual environments. The framework utilises the unique strengths of agent technology such as autonomy, intelligence and collaboration, which enables formation of virtual organisations and adaptive and dynamic coordination of inter-organisational workflows (IOWs). The framework also adopts software component technology to enable plug-and-play style interaction protocols among agent systems. The key ideas of the framework are illustrated using an example case. A proof-of-concept implementation of ADIOF is also presented.